We have to solve f(x) > -1 for f(x)=(x-1)(x+1)/(x+2)(x-2)

f(x) > -1

=> (x-1)(x+1)/(x+2)(x-2) > -1

=> (x-1)(x+1) > -1*(x+2)(x-2)

=> x^2 - 1 > -1* (x^2 - 4)

=> x^2 - 1 > -x^2 + 4

=> 2x^2 > 5

=> x^2 > 5/2

=> x > sqrt 5/2 or x < -sqrt 5/2

**Therefore x lies in (-inf , -(sqrt 5)/2) and ((sqrt 5)/2 , + inf)**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.